2016
DOI: 10.1155/2016/9068257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electroacupuncture on Pain Threshold of Laboring Rats and the Expression of Norepinephrine Transporter and α2 Adrenergic Receptor in the Central Nervous System

Abstract: To observe the effects of electroacupuncture on pain threshold of laboring rats and the expression of norepinephrine transporter and α2 adrenergic receptor in the central nervous system to determine the mechanism of the analgesic effect of labor. 120 pregnant rats were divided into 6 groups: a control group, 4 electroacupuncture groups, and a meperidine group. After interventions, the warm water tail-flick test was used to observe pain threshold. NE levels in serum, NET, and α2AR mRNA and protein expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
1
9
0
3
Order By: Relevance
“…Currently, more and more parturients hope to receive non-pharmacological analgesia because of the potential side effects of pharmacological analgesia including maternal apnoea and neonatal acidosis. 1,2 In this study, EA at Jiaji or SP6+LI4 significantly increased the pain threshold of rats in labour, which was consistent with past reports and our previous studies, 710 implying an analgesic effect of EA at Jiaji and SP6+LI4 on labour pain. It is well known that PGE2 is a key mediator of inflammation and contributes to pain secondary to inflammation and mechanical injury.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Currently, more and more parturients hope to receive non-pharmacological analgesia because of the potential side effects of pharmacological analgesia including maternal apnoea and neonatal acidosis. 1,2 In this study, EA at Jiaji or SP6+LI4 significantly increased the pain threshold of rats in labour, which was consistent with past reports and our previous studies, 710 implying an analgesic effect of EA at Jiaji and SP6+LI4 on labour pain. It is well known that PGE2 is a key mediator of inflammation and contributes to pain secondary to inflammation and mechanical injury.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, there were no differences in pain threshold, serum PGE2 levels or expression of p38 MAPK and PLA2 in the lumbar spinal cord between EA at Jiaji and at SP6+LI4, indicating similar effects and mechanisms of EA at these different sites. We have reported that EA relieves labour pain through the involvement of the spinal dynorphin/κ-opioid receptor system, central nervous norepinephrine transporter and α2 adrenergic receptor expression, 9,10 implying that EA relieves labour pain through multiple mechanisms. Moreover, EA regulates the release of opioids that have a close relationship with pain, 8,9,34 but the underlying mechanisms remain to be fully elucidated and need further study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerosos estudios neuroquímicos realizados en diferentes especies de animales, demuestran que la EA también modula la síntesis y liberación de neurotransmisores, neurohormonas y otros mediadores químicos en diferentes circuitos neuronales situados por encima de la medula espinal en el SNC (Vixner et al, 2012;Hu et al, 2016). Por ejemplo, en los circuitos relacionados con el dolor y la analgesia, la EA modula la síntesis y liberación de los opioides endógenos, endorfinas, encefalinas y dinorfinas, así como también de la serotonina (5-HT), los cuales participan en su acción analgésica demostrada (Hu et al, 2016;Tang et al, 2016). También actúa modulando neurocircuitos límbicos relacionados Moberg et al, 1993;Qu & Zhou, 2006;Tang et al, 2016).…”
Section: Discussionunclassified
“…Por ejemplo, en los circuitos relacionados con el dolor y la analgesia, la EA modula la síntesis y liberación de los opioides endógenos, endorfinas, encefalinas y dinorfinas, así como también de la serotonina (5-HT), los cuales participan en su acción analgésica demostrada (Hu et al, 2016;Tang et al, 2016). También actúa modulando neurocircuitos límbicos relacionados Moberg et al, 1993;Qu & Zhou, 2006;Tang et al, 2016). Como vemos, estos mecanismos neurohumorales de la EA para desencadenar y mantener el trabajo de parto, constituyen una vía de acción larga e indirecta sobre el útero, que necesariamente implica la síntesis de neuromediadores y neurohormonas en los sitios correspondientes del SNC y su posterior liberación a la sangre para finalmente alcanzar y actuar en los receptores del útero.…”
Section: Discussionunclassified